The Bank Card Market: a Comparative Analysis of Ukraine and its Neighboring Countries - Sobolieva-Tereshchenko, Olena (Comparative Economic Research. Central and Eastern Europe, 2018)
The purpose of this study is to define the major determinants of the bank card market to investigate the banking sector of different countries. Using three models of ranking, we discuss what can be used to rank the financial market and how it translates into the ranking of the bank card market. We use comparative analysis to verify our assumption, referring to a total of 8 countries: Ukraine and its neighboring countries. Afterward, we conduct a more in‑depth analysis of two cases (Poland and Ukraine) as two similar bank card markets. The research question is founded on the assumption that for a comparative analysis, it is necessary to use a system of interrelated indicators of bank payment cards, ATMs and POS terminals as the explicative variables.